Guía metodológica para el desarrollo de habilidades motrices en jóvenes de 14 años de la Unidad Educativa Abdón Calderón Muñoz - Gonzales Gustavino, Luis Emanuel (2025)
This studyfocuses on the assessment of motor skills of 14-year-old students in the context of Physical Education class. Its main objective was to develop a methodological guide for the development of motor skills in 14-year-olds of the Abdón Calderón Muñoz de Babahoyo Educational Unit. Apre-experimental design was used, in which a pre-test and post-test were applied, the intervention was through a methodological guide designed for the effect which allowed comparing the results before and after the application of the guide, the sample was composed of 62 eighth-year students of the institutionx=13.7; SD= 0.35: The results indicate that the methodological guide developed responds to the specific needs of 14-year-old students with a p value of 0.00, incorporating activities that promote a comprehensive development of motor skills, this included not only strength and speed exercises, but also activities that promote endurance and motor coordination. In conclusion, the study highlights the importance of a balanced approach in the teaching of motor skills and the need to adapt the methodology to optimize student performance in Physical Education.